The new map department in the National Library of Poland and the first steps to the automation of cataloguing its collections - Szaniawska, Lucyna (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2003)
In 1961, when the Krasinski Palace (the Palace of the Republic) was rebuilt, it was given to the National Library's use. All the departments of the Division of Special Collections were placed in the Palace, including the map department. In 1963 the government made a decision to construct a new building for the National Library of Poland. In the beginning it was planned to move all the collections from the buildings, which they had occupied before, placed in three different districts of Warsaw (including the Division of Special Collections) to the new National Library's building. Its construction started in 1977. But during the works on the site and the move of the collections of books and periodicals dating from the 19th and 20th centuries, it became obvious that those departments, and in particular, their collections, took up too much space, and there was no room for them all. So new plans of enlarging the new building of the National Library were made, but the economic crisis which we are now going through in our country has postponed its development until the distant future. Until now, there is still a remaining part of the Division of Special Collections in the Krasinski Palace, the departments which preserve collections of manuscripts, early printed books, graphics and drawings. Special grand exhibitions are also held in the beautiful baroque rooms there.